Are groups a good thing? Evaluating group associations among vegetable farmers in Freetown, Sierra Leone. Issue 4 (18th May 2016) - Cadzow, Hana; Binns, Tony
ABSTRACT: Urban and peri-urban agriculture (UPA) is a widespread feature in sub-Saharan African cities, and has become particularly important in Freetown, Sierra Leone. Recent surveys have revealed the importance of UPA in Freetown as a method for generating food, income, and employment. Government and NGOs have encouraged urban farmers to group together into farming associations so that advice and inputs can be provided. Little information currently exists about the functioning of these associations, and whether their effectiveness might be improved. This paper draws upon recent field-based research in which the experiences of members in six different farming associations were investigated.